Review of Hyperuricemia as New Marker for Metabolic Syndrome. (16th February 2014) - Billiet, Laura; Doaty, Sarah; Katz, James D.; Velasquez, Manuel T.
Abstract : Hyperuricemia has long been established as the major etiologic factor in gout. In recent years, a large body of evidence has accumulated that suggests that hyperuricemia may play a role in the development and pathogenesis of a number of metabolic, hemodynamic, and systemic pathologic diseases, including metabolic syndrome, hypertension, stroke, and atherosclerosis. A number of epidemiologic studies have linked hyperuricemia with each of these disorders. In some studies, therapies that lower uric acid may prevent or improve certain components of the metabolic syndrome. There is an association between uric acid and the development of systemic lupus erythematosus; the connection between other rheumatic diseases such as rheumatoid arthritis and osteoarthritis is less clear. The mechanism for the role of uric acid in disorders other than gout is not well established but recent investigations point towards systemic inflammation induced by urate, as the major pathophysiological event common to systemic diseases, including atherosclerosis.